2004
DOI: 10.1002/mus.20157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of velocity on maximal torque production in poststroke hemiparesis

Abstract: Impaired torque production is a major physical impairment following stroke, and has been studied extensively in isometric conditions. However, functional use of a limb requires torque production during movement, and the effects of velocity on maximal torque production may be abnormally enhanced in the paretic limb. The purpose of this study was to quantify the effects of movement velocity on maximal torque production during isokinetic, concentric flexion and extension of the elbow in poststroke subjects. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 46 publications
5
38
0
1
Order By: Relevance
“…18 At low velocity (30 /s), no force deficits were found in the paretic biceps or quadriceps muscles relative to the non-paretic side or controls, but force deficits were evident in the paretic hamstrings and triceps muscles. 57,[63][64][65] Similar decreases in force as velocity increased from 30 /s to 120 /s or 180 /s were found in the paretic and nonparetic quadriceps and triceps, 57,64 indicating that the force-velocity relationship was maintained for these muscles or, at least, was maintained at these velocities. Although no difference in the force-velocity relationship was found in the elbow extensors, greater deficits as velocities increased were found in the elbow flexors.…”
Section: Force-velocity Relationshipmentioning
confidence: 57%
See 3 more Smart Citations
“…18 At low velocity (30 /s), no force deficits were found in the paretic biceps or quadriceps muscles relative to the non-paretic side or controls, but force deficits were evident in the paretic hamstrings and triceps muscles. 57,[63][64][65] Similar decreases in force as velocity increased from 30 /s to 120 /s or 180 /s were found in the paretic and nonparetic quadriceps and triceps, 57,64 indicating that the force-velocity relationship was maintained for these muscles or, at least, was maintained at these velocities. Although no difference in the force-velocity relationship was found in the elbow extensors, greater deficits as velocities increased were found in the elbow flexors.…”
Section: Force-velocity Relationshipmentioning
confidence: 57%
“…Although no difference in the force-velocity relationship was found in the elbow extensors, greater deficits as velocities increased were found in the elbow flexors. 57 Lum and colleagues 57 also found that when the elbow flexors were moved from extension to flexion, there were no deficits when the muscle was lengthened; torque deficits were found only late in flexion, when the elbow flexors were shortened. In some cases, the extent of the impairment following stroke was so severe that movement velocities of 300 /s could not be produced, especially in knee flexion.…”
Section: Force-velocity Relationshipmentioning
confidence: 97%
See 2 more Smart Citations
“…Reaching and grasping movements are components of many activities of daily living (ADLs) and are often impaired after stroke. Studies have reported a variety of impairments related to reaching and grasping, including decreased muscle activation and weakness [9][10][11][12], disrupted interjoint coordination [13][14][15][16], decreased smoothness of movement [17][18], and dyscoordination between reach and grasp movements [19].…”
Section: Introductionmentioning
confidence: 99%